Development of Peptide-Based Vaccines for Cancer - Noraini, Abd-Aziz *; Poh, Chit Laa * (Wiley Open Access, 2022)
Peptides cancer vaccines are designed based on the epitope peptides that can elicit humoral and cellular immune responses targeting tumor-associated antigens (TAAs) or tumor-specific antigens (TSAs). In order to develop a clinically safe and more effective vaccine for the future, several issues need to be addressed, and these include the selection of optimal antigen targets, adjuvants, and immunization regimens. Another emerging approach involves the use of personalized peptide-based vaccines based on neoantigens to enhance antitumor response. Rationally designed combinatorial therapy is currently being investigated with chemotherapeutic drugs or immune checkpoint inhibitor therapies to improve the efficacy. This review discusses an overview of the development of peptide-based vaccines, the role of adjuvants, and the delivery systems for peptide vaccines as well as combinatorial therapy as potential anticancer strategies.